Examining the impacts of the COVID-19 pandemic on family mental health in Canada: findings from a national cross-sectional study - Gadermann, Anne C; Thomson, Kimberly C; Richardson, Chris G; Gagné, Monique; McAuliffe, Corey; Hirani, Saima; Jenkins, Emily (BMJ open, 2021)
ObjectivesIn the first wave of the COVID-19 pandemic, social isolation, school/child care closures and employment instability have created unprecedented conditions for families raising children at home. This study describes the mental health impacts of the COVID-19 pandemic on families with children in Canada.Design, setting and participantsThis descriptive study used a nationally representative, cross-sectional survey of adults living in Canada (n=3000) to examine the mental health impacts of the COVID-19 pandemic. Outcomes among parents with children <18 years old living at home (n=618) were compared with the rest of the sample. Data were collected via an online survey between 14 May to 29 May 2020.Outcome measuresParticipants reported on changes to their mental health since the onset of the pandemic and sources of stress, emotional responses, substance use patterns and suicidality/self-harm. Additionally, parents identified changes in their interactions with their children, impacts on their children’s mental health and sources of support accessed.Results44.3% of parents with children <18 years living at home reported worse mental health as a result of the COVID-19 pandemic compared with 35.6% of respondents without children <18 living at home, χ2 (1, n=3000)=16.2, p<0.001. More parents compared with the rest of the sample reported increased alcohol consumption (27.7% vs 16.1%, χ2 (1, n=3000)=43.8, p<0.001), suicidal thoughts/feelings (8.3% vs 5.2%, χ2 (1, n=3000)=8.0, p=0.005) and stress about being safe from physical/emotional domestic violence (11.5% vs 7.9%, χ2 (1, n=3000)=8.1, p=0.005). 24.8% (95% CI 21.4 to 28.4) of parents reported their children’s mental health had worsened since the pandemic. Parents also reported more frequent negative as well as positive interactions with their children due to the pandemic (eg, more conflicts, 22.2% (95% CI 19.0 to 25.7); increased feelings of closeness, 49.7% (95% CI 45.7 to 53.7)).ConclusionsThis study identifies that families with children <18 at home have experienced deteriorated mental health due to the pandemic. Population-level responses are required to adequately respond to families’ diverse needs and mitigate the potential for widening health and social inequities for parents and children.